PENGARUH PERILAKU BERORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. RAYAS TRIPUTRA SEJATI KOTA TANGERANG SELATAN - Anindia Zahra Ramadani; Dr. N. Lilis Suryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of Organizational Behavior (X1) and Compensation (X2) on Employee Performance (Y) at PT. Rayas Triputra Sejati, South Tangerang City. This study uses quantitative research. The sampling technique uses saturated sampling and obtained 122 respondents. Data collection by distributing questionnaires to all respondents. The results of the partial test (T test) show that the Organizational Behavior variable (X1) has an effect on Employee Performance, with t count 6.468> t table 1.660 and a significance of 0.001 <0.05. The Compensation variable (X2) also has a positive and significant effect on Employee Performance, with a t count value of 2.323> t table 1.660 and a significance of 0.001 <0.05. The results of the simultaneous test (F-test) indicate that Organizational Behavior and Compensation jointly have a positive and significant effect on Employee Performance, with an F-value of 20.867 < F-table of 1.660 and a significance level of 0.001 < 0.05. The simultaneous correlation coefficient (R2) of 0.551 indicates a strong relationship between Organizational Behavior and Compensation and Employee Performance, while the coefficient of determination (Adjusted R2) of 0.527 indicates that 52.7% of the variation in Employee Performance can be explained by Organizational Behavior and Compensation, while the remaining 47.3% is influenced by factors outside this study